PENGARUH SEBELUM DAN SAAT ADANYA PANDEMI COVID-19 TERHADAP SAHAM LQ-45 DI BURSA EFEK INDONESIA TAHUN 2020 - Monita Khoiriah; Moh. Amin; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This research was conducted to determine the effect of the Covid-19 Pandemic of the 45 top stocks (LQ-45) listed on the IDX. In this study, the authors used 45 stock samples that were members of the LQ-45 in the 2020 period. The research method used was the Paired Samples T-Test and the Wilcoxon Signed Ranks Test. Based on the results of the tests that have been carried out, it can be concluded that before and after the Covid-19 Pandemic had a significant influence on LQ-45 shares listed on the Indonesia Stock Exchange in 2020. The test results using the Paired Samples T-Test showed that the average variable The abnormal return (AAR) between before and during the Covid-19 pandemic had a significant effect. Meanwhile, the variable Average trading volume activity (ATVA) shows a significant positive effect between before and during the Covid-19 pandemic.Keyword : Social Events, Pandemic Covid-19, Abnormal Return, Trading Volume Activity, Event Study.